Landslides on Ceres: Diversity and Geologic Context. Issue 12 (17th December 2019) - Duarte, K. D.; Schmidt, B. E.; Chilton, H. T.; Hughson, K. H. G.; Sizemore, H. G.; Ferrier, K. L.; Buffo, J. J.; Scully, J. E. C.; Nathues, A.; Platz, T.; Landis, M.; Byrne, S.; et al.
Abstract: Landslides are among the most widespread geologic features on Ceres. Using data from Dawn's Framing Camera, landslides were previously classified based upon geomorphologic characteristics into one of three archetypal categories, Type 1(T1), Type 2 (T2), and Type 3 (T3). Due to their geologic context, variation in age, and physical characteristics, most landslides on Ceres are, however, intermediate in their morphology and physical properties between the archetypes of each landslide class. Here we describe the varied morphology of individual intermediate landslides, identify geologic controls that contribute to this variation, and provide first‐order quantification of the physical properties of the continuum of Ceres's surface flows. These intermediate flows appear in varied settings and show a range of characteristics, including those found at contacts between craters, those having multiple trunks or lobes; showing characteristics of both T2 and T3 landslides; material slumping on crater rims; very small, ejecta‐like flows; and those appearing inside of catenae. We suggest that while their morphologies can vary, the distribution and mechanical properties of intermediate landslides do not differ significantly from that of archetypal landslides, confirming a link between landslides and subsurface ice. We also find that most intermediate landslides are similar to Type 2 landslides and formed by shallow failure. Clusters of these features suggest ice enhancement near Juling, Kupalo and Urvara craters. Since the majority of Ceres's landslides fall in the intermediate landslide category, placing their attributes in context contributes to a better understanding of Ceres's shallow subsurface and the nature of ground ice. Plain Language Summary: Previously, three distinct types of landslides on Ceres, Type 1 (T1), Type 2 (T2), and Type 3 (T3), were identified and classified by their shapes and locations, but most landslides on Ceres do not fall cleanly into those categories based on shape alone. We have analyzed these intermediate landslides to further describe the continuum of flows seen on Ceres. Here, we study their intrinsic properties to gain a greater understanding of Ceres's subsurface properties. Overall, the locations, shapes, and properties of these landslides on Ceres appear to be influenced by ice contained within Ceres's surface and subsurface materials and suggest local ice enhancement is present in some regions, such as near Juling, Kupalo, and Urvara craters. Key Points: Landslides on Ceres have a wide range of morphologies Subsurface ice affects the formation of most landslides on Ceres and influences their morphology Ceres has widespread ground ice with ice enhancements near the poles and within Juling and Kupalo craters